Avaliação experimental e numérica de aeração induzida por tubos Venturi - Macedo, Pedro Augusto Almeida de (2022)
With the growing demand of oxygen by many industries and study areas, as like environmental sanitation, pisciculture, petrochemical, biochemical and pharmaceutical industries, aerators became a really important part of the process by those industries. However, due to the huge amount of consumed energy by aerators, a search for new sources of aeration in those systems became necessary. The present work has, as the main objective, the study of Venturi aerators, which provides systems oxygenation without using any air supplier mechanical equipment. As a pressurized fluid flows through the converging section, there is a progressive increase in the fluid velocity and a drop in the pressure. Geometrically, in a Venturi tube, the change in cross-sectional area occurs from upstream to downstream, due to a progressive diameter reduction (convergent section), followed by a throttled section with a fixed diameter (throat) and, after this section, a gradual diameter expansion (diverging section). In the throttled portion, when the pressure drop became lower than the atmospheric pressure, an air injection occurs, through an orifice connected in the throat. In this study, the methodological approach adopted includes hydraulic theoretical calculations, hydraulic experiments and computational simulations. At first, by performing a factorial experimental design (33) and through statistical tools, a system was evaluated, through theoretical calculations, to determine which, between the variables studied pump power (PB), length (L) and tubulation diameter (D), were having a bigger impact in the process of air suction at the Venturi tube throat. In this regard, the geometrical ratio between the internal throat diameter and the internal inlet diameter (β) was fixed at the value of 0.5. Furthermore, using the variables PB, L e D at a fixed value, through an experimental unit, the Venturi tube applicability with four distinct geometrical ratios (0.2, 0.3, 0.4 and 0.5) was evaluated, by means of: a relationship between volumetric flow rate and the differential pressure in the throat/inlet upstream portion; oxygenation capacity evaluated through an estimation of the volumetric coefficient of mass transfer (KLa). After, in order to complement the experimental analysis, flow numerical simulations were performed with and without air injection at the throat portion, through computational fluid dynamics. The theoretical results, statistically, indicate a bigger influence in the air suction capacity, at the throat section, by the tubulation diameter, between the dependent variables studied (pump power, length and tubulation diameter). Also, a certain influence of the geometric ratio in the pressure drop and air suction, as its value lowered, bigger pressure drop values were evaluated and suction increased by the Venturi aerator, obtaining, through experiments, 1.2.105 Pa for the ratio of 0.2 and 4.4.104 Pa for the 0.5, at the condition of higher flow rate by the experimental unit. Through theoretical calculations, for the ratio of 0.2 and 0.5, the air flow rate obtained was 1.5.10-3 and 4.8.10-4 m3/s, respectively. Beyond that, the results obtained for the differential pressure indicates a correlation between the experimental and numerical results, with a mean deviation of 6.33%. Finally, the KLa obtained was in the range of 0.0033 and 0.0040 s-1, and the best value was found with the geometric ratio of 0.4. Besides that, the Venturi tube is considered viable, due to the possibility of aeration in a liquid medium, becoming thus, an alternative to conventional processes.